Salvage surgery for recurrent carcinoma of the oral cavity: assessment of prognostic factors. Issue 5 (May 2022) - Nandy, K.; Rai, S.; Bhatt, S.; Puj, K.; Rathod, P.; Gangopadhyay, A.
Abstract: Salvage surgery is the most acceptable therapeutic option for disease control of loco-regional recurrences in oral cancers. Prognostic factors need to be assessed to select patients for salvage surgery who would benefit the most. This was a single-centre retrospective observational study conducted between 2015 and 2018. A total of 168 patients with recurrent oral cavity carcinoma who underwent salvage surgery were included for analysis. The primary endpoints of the study were to evaluate overall survival (rOS) after salvage surgery and prognostic factors affecting survival. In this study, the median rOS was 18 months and the median disease-free survival (rDFS) was 14 months. Advanced stage (hazard ratio (HR) 2.387, 95% confidence interval (CI) 1.496–3.808; P = 0.001) and multimodality treatment (HR 1.642, 95% CI 1.139–2.367; P = 0.008) in the initial disease, as well as nodal spread (HR 3.794, 95% CI 1.580–9.111; P = 0.008) and perineural invasion (HR 2.167, 95% CI 1.358–3.455; P = 0.001) in the recurrent disease, were found to adversely affect survival after salvage surgery. With thorough assessment of the prognostic factors and appropriate patient selection, survival may be favourable after salvage surgery for recurrent oral cavity carcinoma.